Experimental study of an effect of plastic deformation on thermal properties of stainless steel. Issue 1 (2nd January 2019) - Zhelnin, M.; Iziumova, A.; Vshivkov, A.; Plekhov, O.
ABSTRACT: The work is devoted to an experimental investigation of an effect of plastic deformation on the thermal diffusivity, the thermal conductivity and the specific heat capacity of AISI 304 stainless steel. To identify the thermal diffusivity and thermal conductivity during mechanical tests the transient technique based on infrared thermography has been used. The important part of the proposed technique is the data processing algorithm that allows us to perform an identification of the characteristics by fitting an analytical solution to the temperature measurements. The solution has been obtained from the heat transfer model approximating real experimental conditions. A verification of the proposed model is conducted by the numerical simulation. As a result of the study, it has been established that the thermal characteristics of the material variate linearly under an increase of the plastic deformation.